Perancangan Press Tool Dengan Memanfaatkan Mesin Press Bending Di Laboratorium Teknologi Produksi Universitas Riau - M. Faisal; Herisiswanto Herisiswanto; Musthafa Akbar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Press tool is an equipment that has a working principle of emphasis by cutting, assembling, or a combination of both. The press tool can produce large quantities of production in a short time. Many kinds of products can be produced by a press tool, one of them is a plate hole. The aim of this study was to obtain the design of the press tool and the structural results of the strength analysis. This research is limited by the position machine of the press bending with dimensions of tool length of 250 cm, bottom seat width of 14 cm, seat thickness of 4.5 cm, height between punch of 30 cm, and engine power of 700 kN. A plate that can be done with a width press tool of 90 mm, a punch diameter of 50.8 with a thickness of specimen max 2 mm. This research was conducted a survey data collection then designs the sketches of component, calculation of machine element, analysis of the structural strength, technical drawing and finish. The material used is ST 50 and mild steel test specimens. The results of calculation was obtained by blangking style of 96.7 kN, cutting style of 120.9 kN, depth of cutting side of 6 mm, safety factor of steering of 1.6 and minimum diameter of 11.10 mm, voltage of spring shear 1214.02 MPa, extension of short spring 60 mm and safety factor of 1.29, clearence dies of 0.24 mm, strength of bolt connection with safety factor 0.47. Based on the analysis of structural strength with a force of 160 kN, the material of components of ST 50 that were declared safe.Keywords: press tool, machine element, analysis of structural, and strength